Calcium coordination environment in precursor species to calcium carbonate mineral formation. (15th August 2019) - Avaro, Jonathan; Moon, Ellen M.; Rose, Jerome; Rose, Andrew L.
Abstract: The local coordination environment in precursors to calcium carbonate minerals has been studied at pH 7.5 and 8.5 by use of a novel fast mixing device with a freeze quench and freeze-drying method coupled to conventional X-ray absorption spectroscopy. Use of rapid reagent mixing and freeze quenching allowed triggering of (pre-)nucleation reactions and stabilisation of calcium carbonate precursors within 18 ms of contact between the reagent solutions. Using this approach, we examined the impact of saturation state and pH on the short-range order of calcium carbonate precursors. Results show that highly hydrated precursor structures characterised by low coordination number form in conditions below the solubility limit of calcite. The first and second coordination shells of these structures furthermore present similarities with the local coordination environment of calcite. Comparisons with previous molecular dynamics simulations suggest that the observed structures present characteristics most similar to simulated clusters possessing a high coordination number in their first shell. Substantial differences were observed between the local coordination environment of structures prepared at pH 7.5 and 8.5, even though both conditions are dominated by bicarbonate, suggesting a critical role for the carbonate ion under the conditions examined. Overall, our findings are consistent with previous work on the existence and structure of calcium carbonate prenucleation clusters and provide further support for the role of non-classical nucleation in these systems.